2008
DOI: 10.1097/aog.0b013e31817cfdf1
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Mode and Severe Intraventricular Hemorrhage in Single, Very Low Birth Weight, Vertex Infants

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
4
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 23 publications
4
36
4
3
Order By: Relevance
“…26 The association between vaginal delivery and IVH is controversial. [26][27][28][29][30] In this case-control study, we found that vaginal delivery was a risk factor for severe IVH. Low superior vena cava flow, resulting from the inability of the immature heart to withstand high systemic resistance after birth, is associated with an increased risk of late IVH.…”
Section: Discussionmentioning
confidence: 84%
“…26 The association between vaginal delivery and IVH is controversial. [26][27][28][29][30] In this case-control study, we found that vaginal delivery was a risk factor for severe IVH. Low superior vena cava flow, resulting from the inability of the immature heart to withstand high systemic resistance after birth, is associated with an increased risk of late IVH.…”
Section: Discussionmentioning
confidence: 84%
“…The association between mode of delivery and the risk of IVH in VLBW singleton pregnancies has been studied, with controversial findings. Although several small studies suggested that cesarean delivery may decrease the risk for IVH in VLBW singleton pregnancies, 37-40 a study of 4658 VLBW newborn infants 41 and other smaller studies [42][43][44] did not find an association between IVH and mode of delivery. Because an association between IVH and mode of delivery in singleton pregnancies has not been established and considering our small sample size, we believe that, at this stage, the findings of our study should be interpreted with caution.…”
Section: Ajogorgmentioning
confidence: 98%
“…Inborn patients compared to those who are transported had a lower incidence of IVH (13.2 versus 27.4) and a lower relative distribution of severe IVH (39.2 versus 44.1 percent) (Mohamed & Aly, 2010). Delivery mode does not appear to affect the risk of severe IVH (Riskin et al, 2008) whereas the presence or absence of labor in cesarean delivery the data are conflicting. In the neonatal care units the efforts must be put on: prompt and appropriate resuscitation of the neonate, avoiding hemodynamic instability, hypoxia, hyperoxia, hypercarbia and hypocarbia.…”
Section: Prevention and Treatmentmentioning
confidence: 47%